Rāsa rasāḷa - Ṛṣabhadāsa,Śāha, Bhānubena (Jaina Sāhitya Prakāśaka Samiti, 2011)
On Śrī Sreṇika rāsa and Śrī Abhayakumāra rāsa, verse work by Rshabhadāsa, 1575-1635, Gujarati poet; includes interpretation along with text
Includes bibliographical references (p. 546-547). - In Gujarati-Schr
Keywords: Gujarati poetry